2010
DOI: 10.1038/mt.2010.191
|View full text |Cite
|
Sign up to set email alerts
|

Expansive Gene Transfer in the Rat CNS Rapidly Produces Amyotrophic Lateral Sclerosis Relevant Sequelae When TDP-43 is Overexpressed

Abstract: Improved spread of transduction in the central nervous system (CNS) was achieved from intravenous administration of adeno-associated virus serotype-9 (AAV9) to neonatal rats. Spinal lower motor neuron transduction efficiency was estimated to be 78% using the highest vector dose tested at a 12-week interval. The widespread expression could aid studying diseases that affect both the spinal cord and brain, such as amyotrophic lateral sclerosis (ALS). The protein most relevant to neuropathology in ALS is transacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
85
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(96 citation statements)
references
References 40 publications
10
85
1
Order By: Relevance
“…Research findings collected from both stroke patients and animal models of stroke have revealed a time-dependent and functional recovery-related shifting of the somatosensorimotor area in both hemispheres. In the early stages (the acute and subacute phases) after stroke, extensive activities appear in the contralesional motor cortex (Dijkhuizen et al, 2001;Tombari et al, 2004), whereas in the recovery stage of stroke (the chronic phase) the somatosensorimotor activities responding to the affected limbs are transferred and reorganized in the ipsilesional cortex near the infarct area (Carmichael, 2012;Sharma and Cohen, 2012;Tombari et al, 2004;Wang et al, 2010a). The greater the involvement of the ipsilesional networks, the better functional recovery is observed (Calautti and Baron, 2003;Carmichael, 2012;Sharma and Cohen, 2012).…”
Section: Introductionmentioning
confidence: 88%
“…Research findings collected from both stroke patients and animal models of stroke have revealed a time-dependent and functional recovery-related shifting of the somatosensorimotor area in both hemispheres. In the early stages (the acute and subacute phases) after stroke, extensive activities appear in the contralesional motor cortex (Dijkhuizen et al, 2001;Tombari et al, 2004), whereas in the recovery stage of stroke (the chronic phase) the somatosensorimotor activities responding to the affected limbs are transferred and reorganized in the ipsilesional cortex near the infarct area (Carmichael, 2012;Sharma and Cohen, 2012;Tombari et al, 2004;Wang et al, 2010a). The greater the involvement of the ipsilesional networks, the better functional recovery is observed (Calautti and Baron, 2003;Carmichael, 2012;Sharma and Cohen, 2012).…”
Section: Introductionmentioning
confidence: 88%
“…Subsequent investigation has consistently confirmed that AAV9-IV administration to newborn mice induces efficient neuronal transduction. Wang et al [82] have documented a maximal transduction of 78% spinal lower MNs. The authors also detected significant transgene expression levels in the brain, both in neurons and glia, which according to Miyake et al [37] are stable for at least 18 months.…”
Section: Neonatal Versus Adult IV Injectionmentioning
confidence: 98%
“…4). The CD45 + /CD11b - immunophenotype with high intensity and round shape was classified as any type of circulating immune cell such as lymphocytes and with low intensity as longitudinal ramified microglia (resting microglia); the CD45 + /CD11b + immunophenotype with high intensity was classified as monocytes, macrophages or reactive microglia/amoeboid (phagocytic) microglia and with low intensity as longitudinal ramified microglia (resting), and the CD45 - /CD11b + immunophenotype as amoeboid (phagocytic) microglia and longitudinal ramified microglia (resting microglia) [4,22,23,24,29]. …”
Section: Discussionmentioning
confidence: 99%